Febuxostat Promoted Dissolution of Radiolucent Nephrolithiasis in Patients with Hyperuricemia - Yunhua, Mao; Hao, Zhang; Ke, Li; Wentao, Huang; Xiaokang, Li; Jie, Situ (Urology Journal, 2020)
Purpose: This study aimed to investigate the efficacy and safety of febuxostat in patients with radiolucent nephrolithiasis. Materials and Methods: From March 2016 to June 2018, data of 96 patients with radiolucent nephrolithiasis and hyperuricemia who referred to the Third Affiliated Hospital of Sun Yat-sen University were retrospectively analyzed. These patients were divided into allopurinol 300mg/d (control), febuxostat 40mg/d (F40) and 80mg/d (F80) groups respectively. All patients took potassium citrate as a combination treatment and had been followed up for at least 6 months. Before treatment and on after 1st, 3rd and 6th month, complete blood count, serum uric acid (sUA), hepatic and renal function as well as ultrasound were carried out. Arthritic and gastrointestinal symptoms were also monitored. Computed tomography was performed before treatment and 6 months after medication. Results: Compared with allopurinol group, F40 group showed no difference in urate-lowering effect, while F80 had the best effect across all the visits (P<0.01). At 6th month, 25(83.3%) cases of F80 group achieved sUA<6mg/ dL, which was better than allopurinol group (18 cases, 58.1%) and F40 group (17 cases, 58.6%). In the dissolution effect of radiolucent calculi, F80 had the best effect, followed by F40 and then allopurinol (P<0.05). No statistical difference was observed in adverse events among three groups. Conclusion: Febuxostat significantly decreased sUA, promoted radiolucent stone dissolution and reduced the total stone number, whereas it did not increase the adverse events.